A study on the role of plasmonic Ti3C2Tx MXene in enhancing photoredox catalysis. Issue 48 (28th November 2022) - Xie, Guanshun; Han, Chuang; Song, Fei; Zhu, Yisong; Wang, Xuanyu; Wang, Jialin; Wu, Zhenjun; Xie, Xiuqiang; Zhang, Nan
Abstract : This work unravels that the plasmon-induced electric field enhancement of Ti3 C2 T x cooperates with the electron-reservoir role to extract photoinduced electrons, affording multichannel electron transfer towards improved photocatalytic efficiency. Abstract : Engineering the spatial separation and transfer of photogenerated charge carriers has been one of the most enduring research topics in the field of photocatalysis due to its crucial role in determining the performances of photocatalysts. Herein, as a proof-of-concept, Ti3 C2 T x MXene is coupled with a typical heterojunction of TiO2 @CdS through a co-assembly strategy to boost electron pumping towards improving the photocatalytic efficiency. In addition to the band alignment-mediated electron transfer in TiO2 @CdS–Ti3 C2 T x heterojunctions, the plasmon-induced electric field enhancement of Ti3 C2 T x is found to cooperate with the electron-reservoir role of Ti3 C2 T x to extract photoinduced electrons. The synergistic dual functions of Ti3 C2 T x promote multichannel electron transfer in TiO2 @CdS–Ti3 C2 T x hybrids to improve the photocatalytic efficiency. These results intuitively show that there is a wide scope to manipulate the spatial separation and transfer of photoinduced electrons by cultivating the fertile ground of Ti3 C2 T x toward boosting the efficiency of solar-to-chemical conversion.